AKTIVITAS ANTIOKSIDAN EKSTRAK TUMBUHAN PAKU EKOR KUDA (Equisetum debile L.) TERHADAP PEROKSIDASI LIPID PLASMA DARAH MENCIT (Mus musculus) - Suryaningrum, Riana Dyah; Puspawati, Ni Made; Astiti, Ni Putu Adriani (Metamorfosa: Journal of Biological Sciences; Vol 4 No 1 (2017)DO - 10.24843/metamorfosa.2017.v04.i01.p08, 2017)
The purpose of this research was to study the antioxidant activity from ethanol extract of horstail ( Equisetum debile L.) in the free radical scavenging in mice blood plasma. The antioxidant activity test was conducted with the DPPH method and measuring the MDA concentration in mice blood. The antioxidant activity test with the DPPH results showed that the ethanol extract of horstail ( Equisetum debile L.) had the antioxidant activity of IC 50 which was 1.604 mg/mL or 1,604 ppm. The statistical analysis result of the MDA blood plasma in mice with various doses (125 mg/kgBM, 250 mg/kgBM, 375 mg/kgBM and 500 mg/kgBM) showed that the 500 mg/kgBM dose extract was able to reduce the MDA concentration in mice blood which given the most amount of exercise.
Keywords: Horstail, antioxidant, DPPH, lipid peroxidation